DIASTASIS RECTI ABDOMINIS AND ITS ASSOCIATED RISK FACTORS IN POSTPARTUM WOMEN - Iqbal, Muhammad Hussain; Hussain, Tanveer; Khalid, Fariha; Ali, Malik Mubashar; Ashraf, Iqra; Nazir, Tehreem (Pakistan Armed Forces Medical Journal, 2020)
Objective: To determine the frequency of diastasis recti abdominis and its associated risk factors in postpartum women. Study Design: Cross-sectional study. Place and Duration of Study: Omar Medical Center Lahore, Yaseen Medical Center Lahore and Social Security Hospital Lahore, from Sep 2019 to Dec 2019. Methodology: This study included 128 participants fulfilling the eligibility criteria. The assessment of diastasis recti abdominis was done manually by a female physiotherapist using single finger, double finger and three finger methods on abdomen at three levels: at the umbilicus, 4.5 cm below and above the umbilicus. Results: The frequency of diastasis recti abdominis out of 128 participants was 97 (75.8%). Out of 128 participants about 38 (29.7%) were primigravida and 90 (70.3%) multigravida. Statistical significance (p=0.015) was found between presence of diastasis recti abdominis and number of pregnancies (gravidity). No association was present between diastasis recti abdominis and delivery method (p=0.09). The p-value (0.56) showed no significant association of diastasis recti abdominis with pelvis floor dysfunction and urinary incontinence. Conclusion: The findings of this study concluded high frequency of diastasis recti abdominis in postpartum women. As the number of pregnancies increased, it decreased the integrity of linea alba and caused the separation of rectus abdominis muscle.